2020
DOI: 10.1061/(asce)gm.1943-5622.0001707
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the State Parameter in Crushable Sands

Abstract: The state parameter (y) measures the distance from the current state to the critical state line (CSL) in the compression plane. The existence of a correlation between both the peak angle of shearing resistance (# $) and peak dilatancy and y is central to many constitutive models used to predict granular soil behaviour. These correlations do not explicitly consider particle crushing. Crushing induced evolution of the particle size distribution influences the CSL position and recent research supports used of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Particle crushing changes the position of the CSL in the compression plane (Bandini and Coop, 2011;Sadrekarimi and Olson 2014). These experimental results were corroborated and extended in DEM simulations by (Ciantia et al 2019, Ciantia andO'Sullivan 2020) using a crushable DEM model calibrated to represent Fontainebleau sand.…”
Section: Introductionsupporting
confidence: 58%
“…Particle crushing changes the position of the CSL in the compression plane (Bandini and Coop, 2011;Sadrekarimi and Olson 2014). These experimental results were corroborated and extended in DEM simulations by (Ciantia et al 2019, Ciantia andO'Sullivan 2020) using a crushable DEM model calibrated to represent Fontainebleau sand.…”
Section: Introductionsupporting
confidence: 58%
“…affected by particle breakage (Ueng and Chen 2000;Coop et al 2004;Russell and Khalili 2004;Zhang and Baudet 2013;Hyodo et al 2016;Yu 2017b;Mao et al 2019;Ovalle and Hicher 2019;Ganju et al 2020), which reduces the dilatancy and peak strength, and enhances the hardening and contraction behaviors of sands (Indraratna and Salim 2002;Hasanlourad et al 2008;Sadrekarimi and Olson 2011a;Liu et al 2016;Yu 2017b;Ciantia and O'Sullivan 2020;Wang et al 2020;Zhang and Luo 2020).…”
Section: Constitutive Modelmentioning
confidence: 99%
“…The macroscopic behaviors (such as the strain softening and volumetric dilation behaviors of the rough interface and the strain hardening and volumetric contraction behaviors of the smooth interface) strongly correlated with the microstructural anisotropy evolution. Ciantia and O'Sullivan (2020) proposed a method to modify the state parameter for crushable soils in the critical state plane that was formed by introducing the grading state index into the compression plane. The employment of this revised state parameter could overcome the limitation that was found during the estimation of the liquefaction susceptibility of crushable soils based on the common state parameter in the compression plane.…”
mentioning
confidence: 99%
“…It was found that a nonlinear CSL in the stress plane correlated with the relative breakage index. A CSL in the compression plane was extended to a critical state plane (CSP) by incorporating the effect of particle breakage, which is similar to that in those studies (Liu and Zou 2013;Ciantia and O'Sullivan 2020). The evolution of particle breakage was expressed as a hyperbolic function of axial strain.…”
mentioning
confidence: 99%